Joint position statement from the Middle East and North Africa and sub-Saharan Africa on continuing to endorse the MAFLD definition - Fouad, Yasser; Ghazinyan, Hasmik; Alboraie, Mohamed; Al Khatry, Maryam; Desalegn, Hailemichael; Al-Ali, Fuad; Zaky, Samy (Elsevier B.V., 2024)
[Abstract Not Available]
Keywords: Africa South of the Sahara; Africa, Northern; Fatty Liver; Middle East; Africa south of the Sahara; alcohol consumption; disease association; fatty liver; human; Letter; metabolic fatty liver; Middle East; North Africa; Africa; fatty liver